Rezension von: Potthast, Barbara (Hrsg.), Christian Friedrich Daniel Schubart - Müller, Carl-Jochen (Zeitschrift für Württembergische Landesgeschichte, 2017)
Barbara Potthast (Hg.), Christian Friedrich Daniel Schubart – Das Werk (Beihefte zum Euphorion 92), Heidelberg: Universitätsverlag Winter 2016. 455 S. ISBN 978-3-8253-6553-0. € 58,–